Association between tumour stroma ratio and other histopathological markers and lymph node metastasis in patients with oral cavity cancer - Prakash Pandit; Vijay Palwe; Sai Krishna U.; Sucheta Gandhe; Yogesh Pawar; Yasam Venkata Ramesh; Raj Nagarkar (The Egyptian Journal of Otolaryngology)
Abstract Background Tumour stroma ratio (TSR) has recently been introduced as a promising prognostic parameter in oral cavity cancers. However, the correlation between TSR and histopathological markers in oral cavity squamous cell carcinoma (OCSCC) patients was not studied extensively. The aim of the present study was to evaluate the prognostic value of TSR from histopathological parameters like tumour size, grade, worst pattern of invasion (WPOI), lymphovascular invasion (LVI), perineural invasion (PNI), peritumoural lymphocytic infiltrates (PLI), and lymph node metastasis (LNM) of OCSCC patients. Methods Prospective data of patients presented with OCSCC from January 2014 to May 2022 were collected and analysed. TSR was correlated with histopathological data. Resultant data was analysed using Statistical Package for the Social Sciences (IBM SPSS Statistics, Version 22.0, IBM Corp., USA). Results The present study included 409 OCSCC patients with a mean age of 49.1 years (range 20–84 years). The majority were male (365, 89.2%) with history of tobacco use (276, 67.5%) and primary as buccal mucosa (263, 64.3%). Of 409 OCSCC patients, moderately (332, 81.2%) differentiated SCC was predominant followed by poor- (42, 10.3%) and well (35, 8.6%)-differentiated SCC. Of 177 (43.3%) LNM-positive patients, where 80.22% (142) are classified as having moderately differentiated SCC, while 19.77% (35) have poorly differentiated SCC. A univariate and multivariate analysis was done to assess, correlate, and investigate the role of TSR and clinicopathological parameters in predicting the LNM in patients with OCSCCs, whereas, on univariate analysis, a significant correlation (p < 0.001) between TSR and tumour size, WPOI, PNI, and PLI was observed. Whereas on multivariate analysis, a significant correlation (p < 0.05) was reported between TSR and tumour size, WPOI, PNI, and PLI. Conclusion Findings from the study indicate TSR has statistically significant association with high-risk factors of OCSCC and can be used as a useful prognostic marker in OCSCC patients. TSR analysis can be used as a simple, cost-effective, easily implemented technique in routine clinical practice, especially in developing countries.